The relationship between world oil price and property related securities in Malaysia - Lau, Yuan Hui, 1992-, author; Lee, Janice Yim Mei, supervisor; Fakulti Geoinformasi dan Harta Tanah (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Sains (Pengurusan Harta Tanah)) - Universiti Teknologi Malaysia, 2017